Surface-area-controlled synthesis of porous TiO2 thin films for gas-sensing applications. (31st January 2017) - Park, Jae Young; Kim, Ho-hyoung; Rana, Dolly; Jamwal, Deepika; Katoch, Akash
Abstract: Surface-area-controlled porous TiO2 thin films were prepared via a simple sol–gel chemical route, and their gas-sensing properties were thoroughly investigated in the presence of typical oxidizing NO2 gas. The surface area of TiO2 thin films was controlled by developing porous TiO2 networked by means of controlling the TiO2 -to-TTIP (titanium isopropoxide, C12 H28 O4 Ti) molar ratio, where TiO2 nanoparticles of size ∼20 nm were used. The sensor's response was found to depend on the surface area of the TiO2 thin films. The porous TiO2 thin-film sensor with greater surface area was more sensitive than those of TiO2 thin films with lesser surface area. The improved sensing ability was ascribed to the porous network formed within the thin films by TiO2 sol. Our results show that surface area is a key parameter for obtaining superior gas-sensing performance; this provides important guidelines for preparing and using porous thin films for gas-sensing applications.